Kærgård og Skovby: Maglemosekulturens regionale flintetraditioner - Skov Khan, Ditte (Kuml, 2025)
Kærgård and Skovby The regional flint traditions of the Maglemose culture This article is about two sites in central Jutland, Kærgård and Skovby, which have shown great potential for elucidating technological traditions during the Late Maglemose period. Kærgård dates to the final centuries of the 8th millennium BC and Skovby to the end of the Maglemose culture, around 6400 BC. These dates are based primarily on microlith typology, supplemented by 14C dates from Kærgård. But the question arises as to whether it is even possible to use lithic technology as a tool for dating Maglemose sites in Jutland (fig. 1). M. Sørensen’s classification of Maglemose technology groups is employed in the interpretation of both sites. Kærgård and Skovby are just two examples from a large assemblage of Maglemose sites found in the Herning area. Multiple sites were revealed in the area around the lake Bølling Sø in conjunction with nature restoration work, and several others were found during investigations preceding construction of the motorway between Herning and Holstebro. Numerous additional sites have also been found in the Silkeborg area in recent years. From a research and interpretation perspective, Maglemose sites in central Jutland present many difficulties, and new examples offering opportunities to refine chronologies are therefore most welcome. The Jutland sites have suffered greater degradation by agricultural activities than those on Zealand, and organic materials are rarely preserved in the sandy soils. Kærgård The Kærgård site comprises a 100 m2 area containing archaeological finds located on a small elevation on the southern bank of the stream Løven Å. A total of 1418 pieces of flint were found here, including 100 examples from the plough soil. The rest of the material is interpreted as being in situ. The flint remains are generally quite small and very fragmented, partially due to exposure to heat. Including fragments, 25 microliths were found which date the site typologically to the end of Phase 2 or the beginning of Phase 3. Combined with an additional 32 microburins, they constitute evidence of intensive microlith production. Fifteen typical and 5 atypical cores were also recovered. The latter were small, one-sided examples with a sloping platform. Several of these had been struck from the side, which is an unusual method. Blades produced by direct, medium-hard percussion numbered 177. Additional flint tools present comprised burins, scrapers and drills. The flint appeared to be distributed in four concentrations, the largest of which had been disturbed by a modern road. The most significant concentration is interpreted as being the result of intensive microlith production around a campfire. Pollen analysis of a turf layer close to the find-rich matrix allowed relative a dating of the finds to around 7000 BC. This concurs well with the typological dating of the flint. The analysis revealed the presence of a dense forest of birch, alder, oak and lime trees in the immediate vicinity, together with a lesser amount of heather indicating some open areas with drier, sandier soil. The site extended over most of the elevation, which also had the highest podzol concentration. The flint was associated with the bleached sand layer. The process of podzol formation could have been promoted by activities at the site. An actual cultural layer is no longer evident, having become diffused with the passage of time. Kærgård was dated with nine 14C dates, of which six fall within the Boreal Maglemose culture – four of these are in the period 7450-7000 BC (figs. 2-11, tabs. 1-2). Skovby The Skovby site comprised three small areas with flint. One of these yielded microliths, which can be placed typologically within the later part of the Maglemose culture. The others contained flint from both the Maglemose culture and the Neolithic period. The soil colouration indicates that these three areas covered a total area of about 100 m². In addition to the microliths, microburins, microblades and burins were also found, and the assemblage is interpreted as representing a single episode at a hunting station. Geological and other environmental analyses were not undertaken due to the lack of preserved organic materials. A total of 689 pieces of flint were found in the three concentrations; a few of these flints dated to the Neolithic. Technological analysis of the eight microliths, plus the blades and cores, indicated that they had been produced by pressure flaking, but the blades and the cores do not reflect that. Typologically, the assemblage of Maglemose flint dates the site to Phase 4/5 of the culture. The finds included six microburins, four cores and 70 blades. Technologically, these are almost identical to the finds from Kærgård (figs. 12-15, tabs. 2-3). Chronology and phase assignation via typology and technology Most of the material analysed from Danish Maglemose culture derives from Zealand. Many sites have been investigated over the years, some of which contained preserved organic materials. They have provided the basis for subdivision of the Maglemose culture. Using typology alone to date sites is problematic and inflexible, especially in the case of disturbed and multicomponent assemblages. Sørensen’s four technological groups, which are linked to Phases 0-5 of the Maglemose culture, show a transition from Phase 2 to 3 around 7000 BC. In the material from eastern Denmark, there is a technological shift at this point to symmetrical blades, conical, channelled cores and scalene triangular microliths, produced by pressure flaking. The origin of this technology is believed to be the Post-Swiderian culture of western Russia and the Baltics. Single component sites from technology group 3 occur at several locations in eastern Denmark, but only a few have been 14C dated. Group 3 becomes less visible the further west in Denmark one looks, and Sørensen suggests a physical border for this group at about the Lillebælt, the strait between Funen and Jutland. The assemblages recovered from Kærgård and Skovby support this conclusion (tab. 4). What does the technology from central Jutland reveal? Both Kærgård and Skovby are unusual sites for central Jutland because they both date to the later part of the Maglemose culture, whereas most of the material from this region is from Phases 0-2. Analysis shows that it is only the microliths that distinguish the two sites chronologically; in most other respects the inventories are very similar. Included in these similarities are the shaping of cores through direct-hard or medium-hard percussion and the choice of raw material, while the blade inventories and micro-burins from both sites also resemble each other greatly. Pressure flaking is not at all in evidence. The sites consequently show both earlier and later technological developments, suggesting a mostly conservative approach to lithic utilisation. The Kærgård microlith assemblage is very similar to contemporaneous material from eastern Denmark. This prompts a discussion of the extent to which the technological element of blade production is restricted geographically. In turn, this indicates a transition from a relatively homogenous culture to one divided into regional groups that have fewer and more sporadic contacts over greater distances. One explanation for this situation could be that the knowledge and skills necessary to replicate specific blade production technologies did not spread as readily as that needed to shape projectile points. The similarities between the microliths recovered from the two sites and those from eastern Denmark could be the result of short-term contact and exchange. The inhabitants of central Jutland may have become more isolated around 7000 BC, perhaps due to changes in climate and landscape. New research on bone points from the Maglemose culture found in bogs divides these into two groups, separated by a hiatus of 600 years, from 8300 to 7700 BC. The hypothesis is that this absence reflects the disappearance of humans, perhaps due to a drastic change in the climate. Kærgård and Skovby are both dated to the same period as the later of these two groups, and perhaps reflect just such change in the form of greater isolation from eastern Denmark. The Kærgård and Skovby sites can serve as templates for interpreting and dating other sites of the Late Maglemose culture in central Jutland. Their assemblages provide a basis for an understanding of technological developments as well as offering dating potential (within certain constraints). It is especially important to recognise and define material from what are often multicomponent sites. Based on the currently available evidence, Maglemose culture technology in central Jutland appears very uniform throughout the 3000 years of its existence, which helps to explain why it has been so difficult to define phases especially in the case of disturbed and mixed assemblages. Additional 14C dates from sealed contexts could aid an understanding of technological developments and dissemination during this period, while new morphological observations could help to refine the chronologies. Investigations of single component, undisturbed sites would greatly assist these endeavours and future road construction schemes and other similar projects, which often cross the river and stream valleys that constitute fruitful locations for Maglemose research, will hopefully provide the opportunity to excavate these types of sites in the future.